Prognostic impact of atrial fibrillation in acute coronary syndromes: results from the ARIAM registry. Issue 2 (1st June 2014) - Almendro-Delia, Manuel; Valle-Caballero, María José; Garcia-Rubira, Juan C; Muñoz-Calero, Blanca; Garcia-Alcantara, Angel; Reina-Toral, Antonio; Benítez-Parejo, José; Hidalgo-Urbano, Rafael
Abstract: Aims: The prognostic ability of atrial fibrillation (AF) in acute coronary syndromes (ACS) is unclear. Studies regarding patient outcomes with respect to the timing of AF are scarce and conflicting. The present study aimed to determine the frequency, predictors and impact on clinical outcome of AF in patients with ACS. Methods: We analysed 39, 237 consecutive patients with ACS included in the ARIAM registry between January /2001 and December 2011. Patients with AF were compared with patients in sinus rhythm. We differentiate between new-onset AF and previous AF cases to analyse mortality and other major adverse cardiac events (MACE) during hospitalization. Results: Of the patients, 2851 (7.3%) developed AF; 1568 (55%) of these were new-onset AF and 1283 (45%) had previous AF. The AF group had a higher risk profile at baseline and poorer clinical presentation at admission than non-AF patients. Compared with previous AF patients, new-onset AF presented with fewer comorbidities, including hypertension, diabetes, prior myocardial infarction, and chronic renal impairment. The inhospital mortality for new-onset AF, previous AF, and non-AF patients were 14, 11.6, and 5.2%, respectively (new-onset AF unadjusted HR 2.19, 95% CI 1.9–2.53, p <0.001; adjusted HR 1.70, 95% CI 1.12–3.4, p <0.001). After propensity score analysis, only new-onset AF persisted as an independent predictor for mortality (HR 1.62, 95% CI 1.09–2.89, p <0.001). Other MACE such as reinfarction, malignant arrhythmias, and heart failure were also more frequent in new-onset AF patients than in previous AF or non-AF patients. Conclusions: These findings suggest that the presence of new-onset AF during ACS is associated with a significant increase in mortality, even after adjusting for confounding variables.